Dividend persistence and earnings management in emerging markets - Orleans Silva Martins; Raíssa Aglé Moura de Sousa; Luiz Felipe de Araújo Pontes Girão (Revista Contabilidade & Finanças, 2021)
ABSTRACT We investigate the relationship between dividend persistence and earnings management, considering the levels of economic performance and risk in emerging countries. Earnings are important for valuation models and dividends have evidence that suggests greater persistence, however, there is no evidence on the effect of earnings management on dividend persistence in emerging countries. Despite the substantial growth of emerging markets in the last decades, the degree of informational efficiency and the legal protection for investors is inferior to developed countries, and this is a potential risk for investors who prefer to receive dividends as a way of avoiding expropriation by managers who can manage the firms’ earnings. We show that the reduction in macroeconomic volatility and the uncertainties concerning a country’s performance and risk improve dividend persistence. Thus, even in the face of earnings manipulations, dividends are better inputs for valuation models. Using the persistence models of Dechow and Schrand (2004) and Lintner (1956), we interact the dividend persistence with firms’ earnings management and some indicators of a country’s economic performance and risk for 7,536 publicly traded firms from 20 countries, included in the Morgan Stanley Capital International (MSCI) Emerging Markets Index from 2000 to 2016. We find that in emerging countries dividends are more persistent than earnings. If a company pays United States dollars (USD) 1.00 in dividends, then, on average, US$ 0.89 will persist into next year’s dividends (for earnings, only US$ 0.76 persists). We find that, in addition to the past dividends and current earnings presented by Lintner (1956), current dividends are a function of earnings management volume because this event reduces dividend persistence.